How vanadium and manganese compounds impact cardiac mitochondrial function - Dolan, Connor C.; Whitcomb, Luke A.; Del Carpio, Edgar; Rose, Lilliana; Chicco, Adam J.; Crans, Debbie C. (Frontiers in Chemical Biology, 2025)
IntroductionVanadium and manganese are two biologically relevant redox-active first row transition metals. Both metals have been associated with protective and deleterious effects in the cardiovascular system depending on the biological context, chemical species and metal oxidation state investigated. Many studies have indicated that these metals elicit their effects in part by influencing mitochondrial function, with potential variations due to their redox properties and complexation.MethodsTo better understand these relationships, we investigated the effects of vanadium and manganese salts (VIVOSO4, NaVVO3, MnIICl2) and acetoacetate (Hacac) complexes (VIVO(acac)2 and MnII(acac)2) on murine cardiac mitochondrial function. Metal speciation calculations were performed to predict the chemical species present under biological assay conditions.Results and DiscussionBoth vanadium and manganese salts decreased rates of mitochondrial respiration in a concentration dependent manner, which was attenuated when the metals were complexed to an organic ligand. In contrast, only VIVOSO4 and VIVO(acac)2 induced significant mitochondrial swelling, with greater sensitivity over NaVVO3, MnIICl2, MnII(acac)2 and free Hacac ligand. Swelling induced by both vanadium(IV) species was fully abolished by inhibition of the mitochondrial calcium uniporter and was partially dependent upon the voltage-dependent anion channel. In addition to the simple monomeric form (VIVO(H2O)52+), a second active vanadium species is the dimer (VIVO)2(OH)5−, while for manganese the main active species is Mn2+. In summary, these studies demonstrate distinct effects of vanadium and manganese on cardiac mitochondrial function that vary in part with the chemical speciation and metal oxidation state.